Eulepida niveata, a new species from Zimbabwe and Mozambique (Coleoptera: Scarabaeidae: Melolonthinae) - Sehnal, Richard (Zootaxa, 2018)
The genus Eulepida Kolbe, 1894 presently contains 22 species (Lacroix 2017, Sehnal 2018) divided on the base of external and aedeagal morphology into three groups (see Lacroix 2010, 2013 for details). Group II is defined by the combination of the following characters: protibia bidentate; antennal club distinctly longer than antennal shaft; pygidium narrow, longer than wide, with a pronounced elongate terminal invagination; and parameres symmetrical, long, evenly curved in ventral aspect (Lacroix 2010). Until recently this group contained three species, E. anatina Brenske, 1896, E. tschindeana Péringuey, 1904 and E. werneri Lacroix, 2010, to which Lacroix & Montreuil (2017) added E. delgadoensis from Mozambique and Sehnal (2018) added E. mbala from Zambia. Shortly after the description of E. mbala I received large series of melolonthines from Zimbabwe and Mozambique, which included another markedly different group II species of Eulepida described below.